The Effectiveness of Problem-Based Learning in Enhancing Reflective-Critical Thinking Skills of Elementary School Students in Science Learning - Surya, Yenni Fitra; Atmoko, Adi; Nusantara, Toto; Masfufha, Aynin; Sumianto, Sumianto (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2025)
The cultivation of reflective and critical thinking skills in elementary science education poses a difficulty, as traditional instructional techniques often restrict students' cognitive engagement and metacognitive awareness. This study seeks to examine the efficacy of problem-based learning (PBL) in improving the reflective and critical thinking abilities of fifth-grade elementary students in scientific education. This research utilized a quantitative methodology with a quasi-experimental design, namely the non-equivalent control group design. The sample comprised 90 students who were randomly allocated to experimental and control groups. The instrument employed was a test of 23 valid items, conducted as both a pre-test and a post-test. Data analysis was performed utilizing descriptive statistics, normality and homogeneity assessments, n-gain analysis, and t-tests. The study's results demonstrate that the experimental group achieved markedly superior post-test scores (M = 83.91; SD = 6.32) in contrast to the control group (M = 70.24; SD = 7.15), with a significance level of p = 0.000. The n-gain value for the experimental group (0.61) was into the moderate range, whereas the control group (0.29) was classified in the low category. These findings indicate that PBL is beneficial in enhancing students' skills in problem identification, hypothesis formulation, evidence analysis, and reflective thinking. This study's originality resides in the empirical validation of PBL implementation at the primary school level, a topic that has seldom been thoroughly examined. The results suggest the need for curriculum change, pedagogical innovation, and professional development for educators in inclusive and reflective fundamental scientific education.